2019
DOI: 10.1111/cns.13279
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic conditioning for the treatment of ischemic moyamoya disease

Abstract: Aims This study investigated the safety and efficacy of remote ischemic conditioning (RIC) on ameliorating the sequelae of ischemic moyamoya disease (iMMD). Methods A total of 30 iMMD patients underwent long‐term RIC and were followed up at 0.5, 1, and 2 years for clinical outcomes, including frequency of stroke recurrence, Patient Global Impression of Change (PGIC) scale, peak systolic velocities (PSV), and cerebral perfusion. Results During the whole RIC treatment process, no RIC‐related adverse event occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…RIC has been shown to improve CBF of patients with chronic circulation insufficiency like ICAS by promoting angiogenesis or arteriogenesis ( 9 11 , 30 , 31 ). A recent single-arm study also observed an improvement of cerebral perfusion in patients with MMD by RIC treatment ( 14 ). This study showed that mCBF of the MCA region was improved in the RIC group.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…RIC has been shown to improve CBF of patients with chronic circulation insufficiency like ICAS by promoting angiogenesis or arteriogenesis ( 9 11 , 30 , 31 ). A recent single-arm study also observed an improvement of cerebral perfusion in patients with MMD by RIC treatment ( 14 ). This study showed that mCBF of the MCA region was improved in the RIC group.…”
Section: Discussionmentioning
confidence: 84%
“…Wang et al reported that daily RIC for 1 year could improve cognitive function and reduce the volume of white matter hyperintensities of small vessel disease ( 13 ). Recently, a single-arm study has reported that RIC relieved ischemic events and improved perfusion in ischemic patients with MMD ( 14 ). However, the efficacy of RIC for patients with MMD is still unknown in a randomized controlled setting.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, repetitive daily RIC, termed chronic RIC, has gained much attention. It is able to confer a continuous and long-lasting effect, and thus, is more beneficial for the treatment of chronic diseases ( Ding J. Y. et al, 2020 ). Although many studies on RIC have been carried out, the underlying mechanism still needs to be elucidated.…”
Section: Remote Ischemic Conditioningmentioning
confidence: 99%
“…It has been reported that a single RIC treatment in preclinical studies significantly enhanced regional CBF after acute ischemic stroke ( Hoda et al, 2012 , 2014 ). Meanwhile, repeated daily RIC is efficient in improving global CBF in chronic ischemia conditions, such as sICAS and Moyamoya disease (MMD) ( Meng et al, 2012 ; Ding J. Y. et al, 2020 ).…”
Section: Role Of Ric In Mitigating Vcimentioning
confidence: 99%
“…12,25 However, these studies mainly included patients with cerebrovascular stenosis, and the follow-up period for most patients was less than 2 years. To the best of our knowledge, this study is the first to reveal the potential effects of RIC in pa-…”
mentioning
confidence: 99%